Teachersâ€™ Perceptions about the Use of Authentic Material in Pakistani EFL Classrooms - Rehman, Atiya; Perveen, Ayesha (Universitas Negeri Makassar, 2021)
This study explores the perceptions of teachers about the use of Authentic Material in Pakistani secondary school English language teaching classrooms. The research was descriptive in nature and used a quantitative approach to collect data through a survey questionnaire from 40 Pakistani Secondary school English language teachers. The questionnaire used was initially adapted from a research done in Hong Kong by Yeung Ting-fai in 2011, under the topic â€œEnglish language teachers' attitudes towards the use of authentic materials in Hong Kong secondary schoolsâ€ but then modified to a larger extent according to the scenario and situation of the Pakistani education system. The data was analyzed through SPSS and descriptive statistics were obtained. The results of this research are significant in Pakistani context. Although many teachers wanted to use Authentic Material in their classes, they were hesitant to do so due to the constraints related to curriculum, examination system and administrative pressure. The study recommends adapting curriculum and examination systems to provide administrative support that can provide space to Pakistani secondary school teachers for using Authentic Material in English language classrooms.